2021
DOI: 10.1039/d0nr07406c
|View full text |Cite
|
Sign up to set email alerts
|

Injectable, self-healing mesoporous silica nanocomposite hydrogels with improved mechanical properties

Abstract: Nanocomposites created by dynamic crosslinking of mesoporous silica nanoparticles to PEG hydrogels represents a promising strategy to confer mechanical strength and rapid self-healing capabilities to hydrogels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…By varying the APTES/nBG ratios (4.2 and 42 μmol mg –1 ), increasing amine concentrations of 5.4 and 7.6 nmol mg –1 on the nBG could be obtained, respectively ( Figure 1 d), as assessed quantitatively using fluorescent labeling with NHS-FITC ( Figure 1 c). 57 Since the density of the amines depended on the APTES/nBG ratio during modification, the amount of reactive moieties for the subsequent functionalization of the particles with peptides could be controlled. Surface amination was further apparent from zeta potential measurements ( Figure 1 e).…”
Section: Resultsmentioning
confidence: 99%
“…By varying the APTES/nBG ratios (4.2 and 42 μmol mg –1 ), increasing amine concentrations of 5.4 and 7.6 nmol mg –1 on the nBG could be obtained, respectively ( Figure 1 d), as assessed quantitatively using fluorescent labeling with NHS-FITC ( Figure 1 c). 57 Since the density of the amines depended on the APTES/nBG ratio during modification, the amount of reactive moieties for the subsequent functionalization of the particles with peptides could be controlled. Surface amination was further apparent from zeta potential measurements ( Figure 1 e).…”
Section: Resultsmentioning
confidence: 99%
“…Many strategies have been developed to improve the mechanical properties of hydrogels. Three important strategies are usually used: controlling the hydrogel concentration, [73] using a dual/interpenetrating network structure, [16a,74] and incorporating nanomaterials into the gel matrix [34,46,61] . In this part, we mainly discuss the improvement of the self‐healing performance, rheological properties, stretchability and toughness of hydrogels by the incorporation of nanomaterials.…”
Section: Influence Of Nanomaterials On the Properties Of Hydrogelsmentioning
confidence: 99%
“…In recent years, some studies have shown that through dynamic covalent interaction, faster self‐healing gels can be prepared, which renders the hydrogel more environmentally friendly and greatly improves the utilization of materials [59b] . With subsequent in‐depth research, people mainly use methods to functionalize the surface of nanomaterials, [34,58] so that they have the conditions to form dynamic covalent interactions. Then, a dynamic covalent reversible reaction between the functionalized nanomaterial and the hydrogel matrix generates dynamic covalent bonds, thereby forming a hydrogel with self‐healing properties.…”
Section: Influence Of Nanomaterials On the Properties Of Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocomposite hydrogel (NC hydrogel), nanomaterials are incorporated in the cross‐linked polymeric chains, is one type of emerging hydrogels to present unique properties compared to traditional polymeric hydrogel. [ 1–4 ] NC hydrogels with different nanomaterials (e.g., carbon‐based nanomaterials, [ 5–8 ] polymer nanoparticles, [ 9 ] inorganic/ceramic nanoparticles, [ 10–12 ] or metal/metal oxide nanoparticles [ 13–15 ] ) present improved mechanical toughness [ 16,17 ] as well as novel performances (e.g., magnetic responsiveness, [ 13,18 ] near‐infrared responsiveness, [ 19–22 ] antimicrobial properties, [ 23,24 ] electricity, [ 25 ] thermal conductivity, [ 26 ] and fluorescence [ 27,28 ] ) for specific applications. Those “smart hydrogels” that respond to internal and external stimuli (e.g., light, [ 29,30 ] pH, [ 31–33 ] temperature, [ 34,35 ] or magnetic field [ 36,37 ] ) have been widely used in tissue engineering, [ 38,39 ] biosensors, [ 40,41 ] and drug delivery.…”
Section: Introductionmentioning
confidence: 99%